Penerapan sIstem Khalifah di Indonesia Tinjauan Resolusi Konflik - Rizqi, Retanisa; Safitri, Khansa Kamila; Muntaha, Muslih Al (IAIN Metro, 2023)
Abstract:If implemented in Indonesia, the caliphate system uses a conflict resolution perspective. This study uses the library research method. The caliphate system differs from other forms of government, such as monarchy, republic, or federation. The caliphate system cannot be implemented through violence but through lawful methods or by asking for help from Ahl al-Nusrah, synonymous with Ahlul Quwwah. In Indonesia, there are hundreds of different tribes, customs, and beliefs, all of which live side by side in peace. This nation was created with a spirit of tolerance and diversity. Therefore, the founding leaders of this nation instilled Pancasila and the 1945 Constitution with this spirit of diversity and tolerance. The Indonesian state has many different religions, so the Islamic Sharia system or caliphate cannot be applied. Pancasila, which exists today, has become the right ideology to be applied in Indonesia.